Dick Kowalczyk welding side arm onto glass polymerizer - Dow Chemical Company (1957)
General view of Dick Kowalczyk welding a side arm onto a glass polymerizer manufactured in the Dow Chemical Company's Glass Fabrication department. Founded in 1925, the department was responsible for the fabrication and repair of specialty glass equipment used at the Company's plant in Midland, Michigan.
Keywords: Welding; Laboratories; Dow Chemical Company; Glass manufacture; Machinery; Glassware; Employees; Kowalczyk, Dick